Air Pollution Levels Related to Peak Expiratory Flow Rates among Adult Asthmatics in Lampang, Thailand - Wanwisa Chujit; Phongtape Wiwatanadate; Athavudh Deesomchok; Khajornsak Sopajaree; Kamal Eldeirawi; Ying I. Tsai (Aerosol and Air Quality Research)
Abstract Asthmatics may suffer harmful health effects from air pollution. This year-long study, which was conducted from November 2015 till October 2016 and resulted in 12,045 data points from 33 participants, assessed the relationships (with a 95% confidence interval [CI]) between measured air pollutant (CO, NO2, O3, SO2, PM2.5 and PM10) concentrations and peak expiratory flow rates (PEFRs) among adults with asthma in the district of Mae Moh in Lampang, Thailand. A positive correlation was found between the mean daily concentration of NO2 from 4 days prior (“lag 4”) and the PEFR upon waking (“morning PEFR”), with an increase of 1 ppb in the former being associated with an increase of 1.34 L min−1 (95% CI: 0.25, 2.44) in the latter. Also, the interaction between NO2 (lag 4) and PM10 (lag 6) was multiplicatively associated with a decrease of −0.015 L min−1 in the morning PEFR, which was also negatively associated with the maximum daily concentration (“max”) of NO2 (lag 2) and that of PM10 (lag 6), with coefficients of −0.07 and −0.013, respectively. Furthermore, when including PM2.5 max in the generalized estimating equation model, only NO2 max (lag 2) and CO max (lag 6) were negatively associated with the morning PEFR, displaying coefficients of −0.08 and −1.71, respectively. O3 max (lag 3) and PM2.5 max exhibited positive relationships with the PEFR before sleeping (“evening PEFR”), with coefficients of 0.078 and 0.029, respectively. Additionally, the average daily PEFR was positively associated with the average daily concentration of NO2 (lag 4), with a coefficient of 0.15, but negatively associated with that of SO2, with a coefficient of −0.47. We also observed a negative relationship between the average daily PEFR and NO2 max (lag 2), with a coefficient of −0.05, but a positive one between the former and O3 max (lag 3), with a coefficient of 0.06. Our results indicate that the delayed—and, in some cases, negative—effects of these pollutants on PEFRs must be considered in health forecasting and that preventative measures should be implemented to control certain emissions at the source.